Tectono-Thermal Evolution of the Red Sea Rift - Boone, Samuel C.; Balestrieri, Maria-Laura; Kohn, Barry (Frontiers in Earth Science, 2021)
The Oligocene-Recent Red Sea rift is one of the preeminent examples of lithospheric rupture in the recent geological past, forming the basis for many models of how continental breakup occurs and progresses to the formation of new oceanic crust. Utilisation of low-temperature thermochronology in the Red Sea Rift since the 1980s has been key to constraining its spatio-temporal evolution, providing constraints for the propagation of strain and geomorphological development of its margins where datable syn-tectonic strata and/or markers are absent. We review the wealth of published apatite fission track and (U-Th-Sm)/He data from along the Red Sea, affording insights into the Oligocene-Recent thermo-tectonic evolution of the Nubian and Arabian margins. A regional interpolation protocol was employed to synthesise time-temperature reconstructions generated from the mined thermochronology data and burial histories produced from vitrinite reflectance and well data. These cooling-heating maps record a series of pronounced episodes of upper crustal thermal flux related to the development of the Oligocene-Recent Red Sea Rift. Assimilation of these regional thermal history maps with paleogeographic reconstructions and regional magmatic and strain histories provide regional perspectives on the roles of tectonism and geodynamic activity in Red Sea formation and their effects on rift margin development.